The Merck Druggernaut : - Hawthorne, Fran (John wiley & Sons, 2003)
"Fran Hawthorne has produced a compelling, detail-rich account of how the once mighty Merck has fallen from its perch atop the drug industry amid the turmoil that has shaken all the players in the business. Anyone seeking to understand the vast changes this critical industry has undergone in recent years should read The Merck Druggernaut." --Hilary Rosenberg, author of The Vulture Investors and A Traitor to His Class "Few business stories involve life and death. This one does, and Fran Hawthorne tells it with insight and verve. This is an important book for anyone who has ever taken a pill or prescribed one (or bought a pharmaceutical share). It ought to be read as carefully as the directions on a prescription bottle." --Firth Calhoun, Editor at Large, Institutional Investor